1992
DOI: 10.1159/000126246
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Growth Retardation on Pituitary Luteinizing Hormone and Hypothalamic Neuropeptide Y in Ovariectomized Sheep

Abstract: The possible role of neuropeptide Y (NPY) in mediating the relationship between pituitary LH secretion and growth retardation due to restricted feeding was examined in ovariectomized (OVX) prepubertal ewe lambs. One specific objective examined whether there was an inverse relationship between concentrations of NPY in four diencephalic brain regions and pituitary LH secretion in ewe lambs 29-30 weeks old which had been growth retarded since 8 weeks and OVX at 24 weeks. Through dietary restriction, body weight w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

1993
1993
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 16 publications
(29 reference statements)
0
11
0
Order By: Relevance
“…PVN and ARC most probably reflects increased NPY transport to these regions, pre sumably arising from increased NPY synthesis in the ARC. Using radio-immunoassay, Ober and Malven [55] evaluated NPY concentrations in the feed-restricted ewe lamb and found elevated peptide concentrations in the POA, MBH and anterior hypothalamus, whereas in ac cordance with the present study, the ME does not tend to reflect such changes [72. 73].…”
Section: Immunohistochemical Interpretationmentioning
confidence: 52%
See 3 more Smart Citations
“…PVN and ARC most probably reflects increased NPY transport to these regions, pre sumably arising from increased NPY synthesis in the ARC. Using radio-immunoassay, Ober and Malven [55] evaluated NPY concentrations in the feed-restricted ewe lamb and found elevated peptide concentrations in the POA, MBH and anterior hypothalamus, whereas in ac cordance with the present study, the ME does not tend to reflect such changes [72. 73].…”
Section: Immunohistochemical Interpretationmentioning
confidence: 52%
“…Hence, an indirect effect of GnRH neurones could be brought about by increased tone or synaptic input of an inhibitory peptide. In this regard, it is most relevant that intracerebroventricular administration of NPY inhibits LH secretion in OVX sheep [79] and NPY terminals con tact GnRH neurones in the POA in this species [80], and Obcr and Malven [55] reported increased NPY concen trations in the POA of ewes with reduced plasma LH caused by dietary restriction. The increased expression of NPY neurones [53] and the increased levels of NPY IR (present study) that are found in the hypothalamus of sheep on a restricted diet might be thought to be related to reduced levels of gonadotropin secretion.…”
Section: Npy Gal Underfeeding and The Secretion O F Gonadotropins mentioning
confidence: 99%
See 2 more Smart Citations
“…7) of intact FR lambs. Increases in in vivo release of NPY after feed re striction have been reported from the paraventricular nu clei of intact lambs and adult ewes by this laboratory [28,29] and from the laterocerebrospinal fluid of FR adult ovariectomized sheep by another laboratory [48], How ever, since we and others [30,49] have recently reported an increase in tissue content of NPY in ME and all other hypothalamic structures, at this time the origin of the NPY increase in the cerebrospinal fluid is not clear.…”
Section: Discussionmentioning
confidence: 80%